Enhancing the professionalisation of student affairs through assessment (Journal of Student Affairs in Africa, 2021)
The past decades have seen an increase in the attention and focus of student affairs work in Africa. As the profession works to strengthen its reputation and value within higher education through conferences, organisations and publications, student affairs professionals can also raise the stature of the profession through work on their individual campuses. Engaging in assessment may be one such opportunity. As a way to create a common language regarding student affairs assessment, this paper provides an overview of the definitions, types and purposes of assessment. The thought is that viewing assessment as an integral, rather than ‘extra’ aspect of student affairs and incorporating these activities within their work, student affairs professionals will not only improve the effectiveness of their work with students but also can help legitimise the field as a profession.
Keywords: assessment; student affairs; best practices; higher education